Efektivitas E-Portofolio Berbantuan Edmodo Terhadap Keaktifan Belajar dan Kreativitas Mahasiswa Pada Matakuliah Desain Grafis - Nurbani, Nurbani; Permana, Ryan (Universitas Hamzanwadi, 2020)
Using paper-based portfolios (PBP) that have been implemented in the Graphic-Design course, it was known that students' activeness and creativity were low yet. It can be seen from the results of the design or student worked were still very simple. The purpose of this study is to determine the effectiveness of E-portfolios assisted by Edmodo on student activities and creativity. The method used in this research is an experiment, and the form of research is a quasi-experiment (quasi-experimental). The population in this study was four classes. The sample in this study consisted of two classes, namely class A (control class) with a total of 28 students and class D (experimental class) with a total of 26 students for the 2019/2020 school year. The sampling technique used is Purposive Sampling. The experimental design used was Post-test Only Control Group Design. The data analysis technique used is the independent sample t-test. Our findings show that the experimental class has better activeness and creativity with Edmodo then the control class with paper-based portfolios. There are differences in learning activeness and creativity of students who utilize e-portfolios thought Edmodo and active learning of students who use PBP in Graphic-Design courses.